PENGARUH REWARD DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN CV. PUTRA MAS REJANG LEBONG - Ika Laudia Sari; Subandrio Subandrio (UM. Bengkulu, 2022)
The purpose of this study was to determine the effect of rewards and work environment on the performance of employees of CV. Putra Mas Rejang Lebong.This research uses descriptive research method with quantitative data analysis. The population in this study were all employees at CV. Putra Mas Rejang Lebong.Based on the results of multiple linear regression, the form of regression equation is Y = 3.708 + 0.373 (X_1) + 0.644 (X_2). The results of the research and hypothesis show that the reward shows the value of t_hit> t_ (Î± / 2) (2,338> 2,026) and (sig Î± = 0.025 <0.050), the work environment shows the value of t_hit> t_ (Î± / 2) (6,138> 2,026) and (sig Î± = 0.000 <0.050). Reward (X1) is 2,338 and Work Environment variable (X2) is 6,138. Conclusion based on the results of research that has been done, there is a positive and significant influence between the variable Reward (X_1) and Work Environment (X_2) together have an effect on the Employee Performance of CV. Putra Mas Rejang Lebong. We recommend that the leader of CV. Putra Mas Rejang Lebong, where the company is expected that in the future the perception of these matters can be of special concern so that in the future employee perceptions of the rewards from the company can be better, after that the work environment is expected in the future this can be material for evaluation and special attention so that the work environment of the the company can increase as well as employee performance.Â Keywords : Reward, Work Environment, and Employee Performance